REFORMASI BIROKRASI DAN TANTANGAN IMPLEMENTASI GOOD GOVERNANCE DI INDONESIA - Setyasih, Endang Try (Globalwriting Academica Consulting & Publishing, 2023)
To be able to achieve prosperity in society, it is necessary to have good governance. One of the steps that can be achieved to achieve this is through bureaucratic reform. This research will be carried out with the aim of looking at how bureaucratic reform is and the challenges in the implementation of bureaucracy in Indonesia. This research is a descriptive qualitative research. The data used in this study comes from various research results or previous studies that still have relevance to the content of this research. The results of this study then found that there were three main problems in the bureaucracy in Indonesia. These problems include internal factors regarding the inability to change themselves, external factors in the form of political intervention, as well as doubts within the community regarding the effectiveness of the policies made. Therefore, it is necessary to have a bureaucratic design that can overcome the various problems above. At least in the short term, the new bureaucratic design needs to experience intensive improvements in order to encourage bureaucratic enthusiasm and performance.